(3JYdjb Ydi JQGcjH dZhjg TGY Hjf GdYdeGA GSJYeGdgGs - (3eMeO HOQ GdOjf Hf jMji GdbQGais ((3eMeO GdeOYh HTdHi GdHQGSi s)
(3ChdgG (B:s
(3CMeO Gddg SHMGfg hJYGdi MeOkG CcKQ ef Cf jMUi hHYO agPg JYdjbI eHjfI dJQGcjH TGY Hjf GdYdeGA ESJYeGdgG s
(3BNQgG (B:s
(3dQaY GdEHgGe hOaY GdEjgGe aEf GdCeQ GdPi de jhVY ajg JUfja s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B2511) s
Keywords: (3GdeLGejYs